Anatomy of # Plandemi Infodemic: A Case Study on Misinformation Diffusion During the Covid-19 Pandemic - POLAT, BURAK; SÜTCÜ, CEM SEFA (My University, 2022)
Just as the COVID-19 pandemic has spread with the transportation networks of the globalizing world, the infodemic is spreading globally with social media networks. The diffusion potential of social media with its complex structure of mass and interpersonal communication provides the distribution of helpful information. Yet, it can also cause the distribution of information pollution. Information pollution can become massive with the intensified interaction between users and cause infodemic. The World Health Organization sees infodemic as a global problem that needs to be tackled as much as the pandemic in terms of human health. It leads to information pollution and misleads people’s attitudes towards the virus and vaccine. After the video titled “Plandemic: The Hidden Agenda Behind COVID-19” was published on social media platforms such as Youtube and Facebook on May 4, 2020, it spread rapidly and became one of the concrete cases of the infodemic. The video spread rapidly with the shares of the viewers in the two days it was broadcast and reached the number of views close to two million. It has drawn the masses into its magic circle by packaging the COVID-19 claims that are voiced by groups prone to conspiracy theories. Although the video was taken down in a slightly short time, the misinformation it contained remained in circulation globally through interactions on social media. In this research, the reflections of the Plandemic video in Turkey were determined by the content produced by the users on Twitter via the #Plandemi hashtag. The primary purpose of the research is to examine how false information is spread in social media by giving examples. Stuctured as a case study, this research conducts network analysis and content analysis to the posts with the #Plandemi hashtag on Twitter. As a result of the network analysis, power-law distribution has been determined in the interaction between users and message production. As a result of the content analysis, it was determined that there was a contextual overlap with the Plandemic video, especially in the theme of insecurity in the health system. In this respect, the study represents an example of the global fluidity of the infodemic while describing how disinformation is spreading in Turkey in the context of COVID-19. Keywords: Plandemic, Infodemic, Information Diffusion, Social Media, COVID-19

Küreselleşen dünyanın ulaşım ağlarıyla COVID-19 pandemisinin yayıldığı gibi sosyal medyanın kullanıcı ağlarıyla enfodemi küresel çapta yayılmaktadır. Sosyal medyanın kitle ve kişilerarası iletişimi iç içe geçiren yapısı ile gelen yayılım potansiyeli yararlı enformasyonun dağıtımını sağladığı gibi bilgi kirliliğinin dağıtımına da sebebiyet verebilmektedir. Bilgi kirliliği, kullanıcılar arasındaki etkileşimin yoğunlaşması ile kitlesel bir hal alarak enfodemiye neden olabilmektedir. Dünya Sağlık Örgütü, bilgi kirliliğine yol açarak insanların virüse ve aşıya karşı tutumunu yanlış yönlendirdiği için enfodemiyi insan sağlığı açısından pandemi kadar küresel çapta mücadele edilmesi gereken bir sorun olarak görmektedir. “Plandemic: The Hidden Agenda Behind COVID-19” (Plandemi: COVID-19’un Ardındaki Gizli Amaç) başlıklı video 4 Mayıs 2020 tarihinde Youtube ve Facebook gibi sosyal medya platformlarında yayınlandıktan sonra hızla yayılarak enfodeminin somut vakalarından biri olmuştur. Video yayında kaldığı iki gün içerisinde izleyenlerin paylaşımları ile hızla yayılarak iki milyona yakın izlenme sayısına ulaşmıştır. Komplo teorilerine yatkın gruplarca dillendirilen COVID-19 iddialarını paketleyerek kitleleri kendine has sihirli çemberine çekmiştir. Video çok kısa sürede yayımdan kaldırılmış olmasına rağmen içerdiği yanlış bilgiler sosyal medyadaki etkileşimler aracılığıyla küresel çapta dolaşımda kalmıştır. Bu araştırmada Plandemic videosunun Türkiye’deki yansımaları Twitter’da #Plandemi etiketi üzerinden kullanıcıların ürettiği içerikler ile tespit edilmiştir. Araştırmanın temel amacı sosyal medyada yanlış enformasyonun nasıl yayıldığını örneklendirerek incelemektir. Vaka analizi olarak yapılandırılan araştırma kapsamında Twitter’da #Plandemi etiketi ile yapılan paylaşımlara hem ağ analizi hem de içerik analizi uygulanmıştır. Ağ analizi sonucunda kullanıcılar arası etkileşimde ve mesaj üretiminde bir güç yasası dağılımı tespit edilmiştir. İçerik analizi sonucunda ise Plandemic videosuyla özellikle sağlık sistemine duyulan güvensizlik temasında içeriksel örtüşme yaşandığı belirlenmiştir. Çalışma bu yönüyle enfodeminin küresel akışkanlığının bir örneğini temsil ederken bir yönüyle de COVID-19 bağlamında dezenformasyonun ülkemizde nasıl yayılmakta olduğunu da betimlemektedir. Anahtar Kelimeler: Plandemi, Enfodemi, Enformasyon Yayılımı, Sosyal Medya, COVID-19
#Plandemi Enfodemisinin Anatomisi: Covid-19 Pandemisi Döneminde Yanlış Bilginin Yayılımı Üzerine Bir Vaka Analizi
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Kitle İletişimi ve Araçları; Social Sciences and Humanities; Sociology; Mass Communications and Mass Media; İLETİŞİM; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); COMMUNICATION; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); İletişim; Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; Communication; General Social Sciences; Social Sciences & Humanities; Plandemic; Infodemic; Information Diffusion; Social Media; COVID-19; Plandemi; Enfodemi; Enformasyon Yayılımı; Sosyal Medya